Bond Strength of Aluminum Oxide Surface Treatment on Sandwich Restoration - Nadia H Hasan; Sawsan H Al-Jubori; Maha A AL-Murad (University of Mosul, College of Dentistry, 2012)
Aims: The aim of this study is to evaluate the effect of aluminum oxide as a surface treatment on shear bond strength of etched and non-etched GIC for sandwich restoration with different types of tooth co-lored restorations .In addition, failure type was assessed. Materials and Methods: Sixty Teflon molds (5mm diameter and 4mm height) of a chemically cured GIC were prepared. They were divided into two main groups 1st control, 2 ed air-abraded with 50μm aluminum oxide particles. Both groups were sub divided into two subgroups 1st control, 2 ed etched with 37%phosphoric acid. Bonding material was applied to the treated surface of all groups and cured. The second split of Teflon mold (3mm di-ameter and 4mm height)was placed onto the prepared specimenEach subgroups (1st control, 2 nd etched with phosphoric acid) were farther subdivided into three subgroups which entrain filled as fal-low: 1st split filled with a tg microhybrid, in 2 ed split filled with tg fine glass, and in 3 rd split filled with Ceram X. Shear bond strength was measured by using Universal Testing Machine, and mode of failure examined by a stereomicroscope. Results: Anova test showed that there was a highly significant difference for all variables except acid etching effect. Aluminum oxide surface treatment displays supe-rior shear (2.280MPa). tg micro hybrid composite and Ceram X showed highest shear bond strength. Conclusions: Phosphoric acid etching did not improve shear value of sandwich restorations, while uses of aluminum oxide surface treatment, tg micro hybrid and Ceram X filling material gave an improve-ment on it. The failures were mainly cohesive within the GIC except tg fine glass was cohesive in fill-ing material itself.